Digital skills and the use of digital platforms in the informal sector: A case study among Jua Kali Artisans in Nairobi in Kenya - Christopher Momanyi; Andrew Rasugu Riechi; Ibrahim Khatete (International Journal for Research in Vocational Education and Training (IJRVET), 2024)
Context: For many businesses, one of the key indicators in their management is the adaptation of Information Technology in their operations. In Kenya, there has been a phenomenal growth in access to mobile phones, by June 2023, over 66 million mobile phones were connected to various telecommunication operators of which 58.3% were smart phones constituting 67.1% of internet connections. There are many digital technologies which can be adapted to facilitate the processing, dissemination, and access of information. The modern world has become competitive due to the uptake of Information Technology as one of the main business management skill, with the availability of smart phones and many applications that are easily available and easy to use. One of the main beneficiaries of Information Communication Technologies (ICTs) is the Jua Kali artisans who are a key player in the Kenyan economy. Entrepreneurial competencies help the growth of businesses along the dimension of innovation. Kenya intends to entrench the use of Information Technology for public service delivery, business, skills, and innovation. The Jua Kali sector cannot be ignored, it contributes more than 80% of the total employment in Kenya. Approach: This research was carried out in the Eastlands of Nairobi, Kenya. Data were collected using a questionnaire, an interview and observation schedule. The study used an interview schedule to collect data from Jua Kali artisans carrying out their artisan businesses in the Eastlands of Nairobi and a questionnaire survey to collect data from a sample of identified Nairobi residents who had engaged an artisan to work for them six months prior to the research. Findings: The research established that most Jua Kali artisans acquired their skills in the Jua Kali sector by apprenticeship (86.3%) while a small percentage (12.7%) trained in Technical Vocational Education Training (TVET) institutions while a further one percent were trained by their former employers. Most of the artisans had attained the basic formal education qualifications i.e. primary education (27.9%) and secondary education (47.6%). The Chi-square (χ²) test was used to test the relationship between use of the basic social media digital platforms in business management and the formal education attained by artisans owning artisan businesses. Conclusion: At 0.05 level of significance (α) the research established that there is a significant relationship between the adaptation of digital platforms in business management and the formal education attained by the artisans.
Keywords: 330; Digital Skills and Digital Platforms; Informal Sector; Jua Kali; Kenya; Small and Medium Size Enterprises; VET; Vocational Education and Training